IMPLEMENTASI KUALIFIKASI ALKITABIAH PENGAJAR SEKOLAH MINGGU DI GEREJA KRISTEN SETIA INDONESIA SEKTOR PAHAUMAN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK KALIMANTAN BARAT - Crianata Chewy Clorida; Ari Upu Telo (Universitas Kristen Immanuel, 2024)
This research is titled ‘Implementation of Biblical Qualifications for Sunday School Teachers at Setia Indonesia Christian Church in Pahauman Sector, Sengah Temila District, Landak Regency, West Kalimantan’. The background of this research is the absence of a clear implementation of biblical qualifications for Sunday School teachers. This research uses an ethnographic approach, a methodology in the descriptive study of culture and society. Ethnography is a form of qualitative research that focuses on describing the culture of a group of people, analysing key results, and drawing key conclusions. The key findings of this study include a taxonomy analysis that classifies empirical data into intellectual, moral, emotional, spiritual, practical, existential and vocational categories. The results showed the existence of a taxonomy of Teaching Proficiency Qualification principles. The conclusion of this thesis is that the principle of vocational qualification is a gift or grace of God given for those who believe in Him for the glory of His name. The principle of teaching qualification is the ability possessed by a person to preach the truth of God's Word. The teaching integrity qualification refers to the concepts of integrity, honesty, and consistency.